Local analysis of the grain and grain boundary contributions to the bulk dielectric properties of Ca(Cu3−yMgy)Ti4O12 ceramics: Importance of the potential barrier at the grain boundary. Issue 6 (May 2016) - Nautiyal, A.; Autret, C.; Honstettre, C.; De Almeida-Didry, S.; El Amrani, M.; Roger, S.; Negulescu, B.; Ruyter, A.
Abstract: The present work focuses on two aspects related to the synthesis and the dielectric properties of CaCu3 Ti4 O12 (CCTO) ceramics. Effective strategies able to synthesize high quality CCTO, with reduced dielectric losses and high relative permittivity, are achieved by the substitution of Cu ion by Mg one in the crystal. Ca(Cu3− y Mg y )Ti4 O12 ceramics have been synthesized by conventional mixed oxide method involving CCTO and MgO. This approach is found to drastically reduce the synthesis time by lowering the eutectic point of CCTO as a result of the small fraction (1–3 wt%) of MgO added to the mixture. Experimental data have been used to successfully confirm this substitution and the only presence of CuO at grain-boundaries. The role of grain and grain boundary contributions on the dielectric properties of ceramics are investigated. It is found that samples containing 1% MgO lead to excellent relative permittivity values of the order of 3.5 × 10 4 . In these substituted ceramics, extracted relative permittivity values are found to be extremely stable, with low loss tangent (<0.06), up to 100 kHz at room temperature. From the various samples investigated, the optimized ceramics are found to contain large grains (≥15 μm). Local intra-grain and inter-grain electrical transport measurements show that the grains and their respective grain boundaries exhibit metallic and semiconducting behaviors, respectively. This approach confirms the crucial role of the potential barrier at the grain boundary in determining the dielectric properties of such Ca(Cu3− y Mg y )Ti4 O12 ceramics.